Subwavelength structures for taper waveguides. Issue 1 (1st December 2022) - Lourenço, Paulo; Fantoni, Alessandro; Costa, João; Fernandes, Miguel; Vieira, Manuela
Abstract: In Photonic Integrated Circuits (PICs) it is often necessary some sort of mismatch adaptation between waveguides of different cross-sections. There are several instances of such a designing constraint, being the vertical coupling between the PIC and an optical fibre probably the most representative of all examples. Here, the beam of electromagnetic energy inside the PIC must be inserted/extracted through/to an optical fibre. Typical core diameters are approximately 10 μm and 5 μm, for single mode optical fibres operating in the near infrared and visible wavelengths, respectively. On the other hand, the optical interconnects linking individual structures in PICs are usually single mode waveguides, 400 to 500 nm wide and a few hundreds of nanometres thick. This presents a bidimensional mismatch between the optical fibre and the single mode waveguide within the PIC, that requires both lateral and longitudinal beam expansions. In this work, we have approached the lateral expansion of the fundamental mode propagating in a single mode waveguide, at the operating wavelength of 1550 nm and being coupled out into an optical fibre, through a grating structure 14.27 μm wide. To this end, we have designed and simulated a subwavelength metamaterial planar structure, which is able to expand laterally the fundamental mode's profile from 450 nm to 14.27 μm, within 11.1 μm. Furthermore, we will be presenting the results obtained when comparing this structure with several linear inverted taper waveguides, regarding coupling and propagation efficiencies. Namely, we compared the coupling efficiencies of the modes propagating in an 100 μm long waveguide, when being excited by the analytically calculated fundamental mode and the fields obtained at the end of the designed structure. The results obtained for the designed structure 11.1 μm long and the calculated fundamental mode showed a coupling efficiency of -1.53 dB and -1.20 dB, respectively.